Roeder’s Knot: Solution to Intra-Corporeal Knot Tying - Faisal Murad , Qasim Ali , Syeda Aimen Masiha , Syed Muhammad Ali Shah , Amna Ilyas , Sundas Younas ,.Amna Anwaar , Asif Zafar (Journal of Rawalpindi Medical College, 2013)
Background: To evaluate the security and diversity of application of Roeder’s knot. Methods: In this prospective study patients (n=771) undergoing laparoscopic surgery, along with application of Roeder’s knot, were included. The formula for making the Roeder’s knot was (1:3:1) ‘one hitch, three winds and one locking hitch’. Loop was made around a post and then a simple knot was made. With the shorter end, three winds were made around both posts and were secured with the last half hitch. Excess length of the string was trimmed . Knot was held in the grasper and was slided down the trocar into the abdominal cavity. Once inside the abdominal cavity, the structure to be ligated, was placed through the loop. Free end of the string was passed thorough the eye of a knot pusher and knot pusher was slided through the trocar and knot was tightened. End of the knot was trimmed with scissors . For a structure that is not blind ended (eg. an artery or cystic duct), the thread was passed under the structure. Both ends were taken out, loop was tied in a similar manner and was then tightened with knot pusher. To tie the knot, over a suture, needle was brought outside and procedure was repeated. Results: Roeder’s knot was placed in a total of seven hundred and seventy one cases out of total 1883 procedures performed during the study period. The time to assemble the knot was 33 seconds. The time to place a pre-tied knot was two minutes three seconds. The time to assemble and place Roeder’s knot in laparoscopic appendectomies averaged about 2 minutes 36 seconds. It took an average of 3 minutes 40 seconds to assemble and place it in laparoscopic cholecystectomies. While time to place a traditional square knot intra-abdominally averaged about 4 minutes and 39 seconds. In all 771 cases where the Roeder’s knot was placed,an incidence of knot slippage or hematoma formation was not observed. Roeder’s knot was applied in all appendectomies, laparoscopic cholecystectomies in which cystic duct diameter was greater than clips and hernial sac not reduced completely. Conclusion: Roeder’s knot is easy to assemble and place, secure and is a cost effective alternate to intra-corporeal suturing and staples during laparoscopic surgeries.